The role of abortion in explaining ethnic fertility differentials in Vietnam - TEERAWICHITCHAINAN, Bussarawan (Institutional Knowledge at Singapore Management University, 2009)
Until recently, Vietnam had the highest abortion rate in Asia. Abortion–mostly provided by the government—is believed to have contributed significantly to the country’s remarkable fertility decline over the last three decades. Despite the overall fertility decline, fertility rates vary across Vietnam’s 54 ethnic groups. The majority Vietnamese and ethnic Chinese, who together account for 85% of Vietnam’s total population, have total fertility rates below the replacement level. Meanwhile, other ethnic minority groups such as Dao and Hmong, who are disproportionately poor and live in remote, isolated areas, have the total fertility of 3.6 and 7.1 respectively. Analyzing the 1999 Census and 2001-2002 Vietnam National Health Survey, we examine proximate determinants of fertility across ethnic groups using the model proposed by Bongaarts (1978). We focus on the role of abortion, particularly the variations in access to abortion across various ethnic groups, in describing different fertility levels in Vietnam.